2013
DOI: 10.1097/cej.0b013e328354d324
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness features and outcomes of true interval cancers

Abstract: The question of whether screen detection confers an additional survival benefit in breast cancer is unclear and subject to several biases. Our aim was to examine the role of the diagnostic method (screen-detected, symptom-detected, and true interval cancers) and the clinical-pathological features in relapse-free survival and overall survival in breast cancer patients. We included 228 invasive breast cancers diagnosed in Barcelona from 1996 to 2008 among women aged 50-69 years. Ninety-seven patients were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
1
23
1
Order By: Relevance
“…50 In keeping with these findings, they concluded that clinically-detected BC especially where these are true interval cancers had worse prognosis and poorer survival than screen-detected BC even after adjustment for clinical-pathological variables. 50 Porter and colleagues 48 compared the features of interval BCs by radiological classification, and although they observed differences in the histological characteristics (shown in Table 3) there was no significant survival difference between interval BC radiological types ( p  = 0.64).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…50 In keeping with these findings, they concluded that clinically-detected BC especially where these are true interval cancers had worse prognosis and poorer survival than screen-detected BC even after adjustment for clinical-pathological variables. 50 Porter and colleagues 48 compared the features of interval BCs by radiological classification, and although they observed differences in the histological characteristics (shown in Table 3) there was no significant survival difference between interval BC radiological types ( p  = 0.64).…”
Section: Resultsmentioning
confidence: 74%
“…Domingo and colleagues 14, 50 conducted several studies examining the characteristics of interval BCs; one of these evaluated 2245 invasive BCs and clearly showed that interval BCs had more advanced tumours than screen-detected BCs (additional details by interval BC category shown in Table 3). 14 In an earlier study of 228 invasive BCs diagnosed among Barcelona women aged 50–69 years, Domingo et al 50 also found that disease-free survival rates (at 5 year follow-up from diagnosis) for screen-detected, true interval, and symptom-detected BC were 87.5%, 64.1%, and 79.4%, respectively, and overall survival rates were 94.5%, 65.5%, and 85.6%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer that is diagnosed in younger women tends to be more aggressive and more likely to evade detection with screening mammography than in older women (14,30). In our sample of recently screened patients, as expected, SADRS was more likely in younger women.…”
Section: Discussionmentioning
confidence: 99%
“…Interval cancers tend to have poorer stage and poorer prognosis as one would expect (Biesheuvel et al , 2011; Nagtegaal et al , 2011; Domingo et al , 2013). Interval cancer rates are in the order of 2–3 per 1 000 screened in the UK programme (Bennett et al , 2011).…”
Section: Discussionmentioning
confidence: 89%